Simulação da oferta e demanda de recursos hídricos nas bacias dos rios piracicaba, capivarí e jundiaí: Uma análise em dinâmica de sistemas - Sánchez-Román, Rodrigo Máximo [UNESP]; Zolin, Cornélio Alberto; González, Alba María Guadalupe Orellana; Folegatti, Marcos Vinicius (My University, 2012)
A dynamic systems water resources simulation model was developed as a tool to help to analyze water resources management alternatives for the Piracicaba, Capivari and Jundiaí River Water Basins (BH-PCJ). Different politics policy were simulated for 40-year. The model estimates water supply and demand, as well as contamination load from several consumers. Six runs were performed using average precipitation value, changing water supply and demand, and different volumes diverted from BH-PCJ to BH-Alto Tietê For the Business as Usual, the Sustainability Index went from 0.41 in 2010 to 0.22 by 2050; the Water Use Index changed from 80.7% in 2010, to 125.5% by 2050; and the Falkenmark Index changed from 1,302 m 3 person -1 year -1 in 2010 to 774 m 3 P -1 year -1 by 2050. It was noticed that sanitation is one of the biggest concerns in the near future at PCJ River Basin.

Utilizando um modelo de simulação em Dinâmica de Sistemas desenvolvido como ferramenta para auxiliar na análise das alternativas para a gestão dos recursos hídricos, simulou-se o efeito de diferentes políticas de gestão ao longo de 40 anos nas bacias hidrográficas dos rios Piracicaba, Capivari e Jundiaí (BH-PCJ). Através deste modelo foram simulados a disponibilidade e demanda de água, bem como as cargas contaminantes provindas dos diferentes setores usuários. Seis cenários foram simulados utilizando-se o valor da precipitação média anual, mudanças na disponibilidade e demanda de água e a vazão revertidas das BH-PCJ para a Bacia Hidrográfica do Alto Tietê (BH-AT). Para o cenário Business as Usual, em 2010 o Índice de Sustentabilidade que era de 0,41 em 2010 diminuiu até 0,22 em 2050; o Índice de Falkenmark, que era de 1.302 m3 hab-1 ano-1 em 2010, passou a ser de 774 m3 hab-1 ano-1 em 2054; e o Índice de Uso da Água aumentou de 80,7% em 2010, para 125,5% em 2050. Observou-se que as questões relativas ao saneamento se afiguram como sendo as mais importantes para a gestão dos recursos hídricos nas BH-PCJ.
Water balance simulation for the Piracicaba, Capivarí and Jundiaí River Basins: A system dynamic approach
Keywords: Modeling; Sustainability; Systems dynamic; Water resources; basin management; computer simulation; modeling; policy implementation; sanitation; sustainability; water budget; water demand; water resource; water supply; water use; Brazil; Capivari Basin; Jundiai River; Piracicaba; Sao Paulo [Brazil]